2019
DOI: 10.12968/ijtr.2017.0137
|View full text |Cite
|
Sign up to set email alerts
|

Independently getting off the floor: a feasibility study of teaching people with stroke to get up after a fall

Abstract: Background: Falls are common among stroke survivors but many are not taught how to get up again. A technique from Action for Rehabilitation following Neurological Injury (ARNI) addresses this problem. We investigated the feasibility and safety of teaching this technique to stroke survivors. Methods: Stroke survivors (mean 7.1 years post-stroke) with mild-to-moderate disability (mean modified Rankin Score 2.4), who could get up with assistance but not independently, received up to six sessions of training to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…One UK survey found that practical demonstrations were reported by only 14/231 (6%) of falls services [ 13 ], and UK audit data found in 2010 that only 4% of fallers in rehabilitation programmes were taught how to get up [ 14 ]. Anecdotally there appears to be some reluctance to teaching techniques for getting up off the floor - possibly due to a lack of confidence from both older people and therapists, although there is evidence that it is feasible and acceptable to teach this to inpatients, community-dwelling older people and stroke survivors [ 15 – 17 ]. One method commonly used, called “backward chaining” breaks the activity of getting down to and up from the floor into smaller steps, with the last step being taught and achieved first [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…One UK survey found that practical demonstrations were reported by only 14/231 (6%) of falls services [ 13 ], and UK audit data found in 2010 that only 4% of fallers in rehabilitation programmes were taught how to get up [ 14 ]. Anecdotally there appears to be some reluctance to teaching techniques for getting up off the floor - possibly due to a lack of confidence from both older people and therapists, although there is evidence that it is feasible and acceptable to teach this to inpatients, community-dwelling older people and stroke survivors [ 15 – 17 ]. One method commonly used, called “backward chaining” breaks the activity of getting down to and up from the floor into smaller steps, with the last step being taught and achieved first [ 18 ].…”
Section: Introductionmentioning
confidence: 99%